Antibiotic Sensitivity Pattern in Blood Culture Positive Typhoid Fever - Waqas, Muhammad; Ismail, Tahseen; Naseem, Farheen; Zeb, Mian Rahmat; Hanif, Hafiz Haseeb; Farrukh, Ghazal; kousar, Ayesha (Journal of Neonatal Surgery, 2025)
Background: Salmonella enterica serotype Typhi is a major cause of typhoid fever, a leading health problem in low and middle income countries. Rising antibiotic resistance makes for tough effective treatment that highlights the need for better information on local antibiotic sensitivity patterns to manage. Objective: To asses antibiotic Sensitivity Pattern in Blood Culture Positive Typhoid Fever Materials and Methods: This cross sectional study was conducted at Saidu Medical College during June 2022 to August 2024. Patients with confirmed blood culture-positive typhoid fever were selected. Blood samples were collected and antibiotic susceptibility testing was performed using the standard disc diffusion method, targeting commonly prescribed antibiotics such as ciprofloxacin, ceftriaxone, and azithromycin. Sensitivity and resistance rates were recorded and analyzed. Results: Mean age was 26.45 ± 15.74 years and mean duration of fever was 9.72 ± 6.97 days.The analysis of antibiotic sensitivity patterns among 132 blood culture-positive typhoid cases reveals varied effectiveness across the antibiotics tested. Azithromycin demonstrated the highest sensitivity, with 122 cases (92.4%) sensitive and only 10 cases (7.6%) resistant, making it the most effective treatment option. Meropenem showed 100% sensitivity across all cases (132), indicating its potential as a highly reliable choice, though typically reserved for severe cases due to its broad-spectrum activity. Conclusion: Results of this study highlights the changing patterns of antibiotic sensitivity in typhoid fever, and emphasizes the need for continuous monitoring and updated guidelines of antibiotic use. Third generation cephalosporins are preferred treatment (with caution regarding fluoroquinolone use due to high resistance rates), the findings suggest